Agricultural commercialization, land expansion, and homegrown land-scale farmers: Insights from Ghana - Chapoto, Antony; Mabiso, Athur; Bonsu, Adwinmea (International Food Policy Research Institute, 2013)
The past decade has seen several African countries increasing their agricultural growth, a trend largely underpinned by increases in land area cultivated instead of productivity increases. Meanwhile, scholars debate whether Africa should pursue a strategy of large-scale or smallholder farms, paying little attention to a special group of smallholder farmers who have transitioned to become medium- and large-scale farmers. This study, therefore, begins to analyze this group of farmers, using qualitative data from in-depth interviews and focus group discussions in Ghana. We analyze their characteristics, ingredients of farm-size expansion, and commercialization.